Regulation of the SIAH2-HIF-1 Axis by Protein Kinases and Its Implication in Cancer Therapy - Xu, Dazhong; Li, Cen (Frontiers in Cell and Developmental Biology, 2021)
The cellular response to hypoxia is a key biological process that facilitates adaptation of cells to oxygen deprivation (hypoxia). This process is critical for cancer cells to adapt to the hypoxic tumor microenvironment resulting from rapid tumor growth. Hypoxia-inducible factor 1 (HIF-1) is a transcription factor and a master regulator of the cellular response to hypoxia. The activity of HIF-1 is dictated primarily by its alpha subunit (HIF-1α), whose level and/or activity are largely regulated by an oxygen-dependent and ubiquitin/proteasome-mediated process. Prolyl hydroxylases (PHDs) and the E3 ubiquitin ligase Von Hippel-Lindau factor (VHL) catalyze hydroxylation and subsequent ubiquitin-dependent degradation of HIF-1α by the proteasome. Seven in Absentia Homologue 2 (SIAH2) is a RING finger-containing E3 ubiquitin ligase that stabilizes HIF-1α by targeting PHDs for ubiquitin-mediated degradation by the proteasome. This SIAH2-HIF-1 signaling axis is important for maintaining the level of HIF-1α under both normoxic and hypoxic conditions. A number of protein kinases have been identified to phosphorylate SIAH2 thereby regulating its stability, activity, or substrate binding. In this review, we will discuss the regulation of the SIAH2-HIF-1 axis via phosphorylation of SIAH2 by these kinases and its potential implication in cancer biology and cancer therapy.